Construction Method and Verification of High Precision Ground Time Synchronization Links for 5G Mobile Base Stations - Yu WU (Guangtongxin yanjiu, 2021)
To meet the demand of 5G mobile base stations and edge computing nodes for high-precision ground timing system, the construction method of end-to-end ground time synchronization links and the subsequent time synchronization network planning ideas are proposed, which do not rely on satellite timing system. The feasibility of the proposed method is verified by conducting evaluation experiments in the present 5G mobile network of SuZhou, which demonstrate the high and stable time accuracy within 24.8 ns for 72 hours. Key issues such as satellite independent time synchronization network are also analyzed to point out the future improvement direction.